ByzRev 02.2020.018: Marc. D. Lauxtermann – Ida Toth (Hgg.): Inscribing Texts in Byzantium. Continuities and Transformations: (Society for the Promotion of Byzantine Studies, Publications 23). London – New York: Routledge 2020. - Kubina, Krystina (The Byzantine Review, 2020)
Marc D. Lauxtermann – Ida Toth (Hgg.): Inscribing Texts in Byzantium. Continuities and Transformations (Society for the Promotion of Byzantine Studies, Publications 23). London – New York: Routledge 2020. XXV, 381 pp. – ISBN: 978-0-367-24613-6 (£ 120.00)